PENGARUH PRICE DISCOUNT TERHADAP IMPULSE BUYING - Septian Wahyudi (UIR Press, 2017)
In marketing products to be accepted in the target market, Azwa Perfume has several strategies in the form of programs related to price discount among others, Member Disc (10% discount for active members and recorded by Azwa Perfume). Partner Disc (10% discount for other product / service members who have partnership with Azwa Perfume). Member Birthday Disc (35% discount special for members who are birthday). Ladies Day (Addition of 20% perfume every Thursday specifically for women consumers). Azwa Special Kartini (Buy 2 free 1 applies to all products on 21 April) Anniversary Azwa Perfume (50% All Item Discount during Azwa Perfume anniversary celebration every October 1-7). Discount Rp 100.000, - special to customers who use Mandiri Card. 10% discount on Culinary and Shopping Festival. Special Price (Discount) Year-End for some types of perfume (24-31 December 2016). Price discount is a discount if the payment is made more quickly than the credit term. The result of the regression calculation shows that the hypothesis is accepted by indicating that the price discount has an effect on the impulse buying in azwa parfume Pekanbaru.